Study on tinnitus-related electroencephalogram microstates in patients with vestibular schwannomas - Zhang, Chi; Wang, Xiaoguang; Ding, Zhiwei; Zhou, Hanwen; Liu, Peng; Xue, Xinmiao; Wang, Li; Jiang, Yuke; Chen, Jiyue; Shen, Weidong; Yang, Shiming; Wang, Fangyuan (Frontiers in Neuroscience, 2023)
Tinnitus is closely associated with cognition functioning. In order to clarify the central reorganization of tinnitus in patients with vestibular schwannoma (VS), this study explored the aberrant dynamics of electroencephalogram (EEG) microstates and their correlations with tinnitus features in VS patients. Clinical and EEG data were collected from 98 VS patients, including 76 with tinnitus and 22 without tinnitus. Microstates were clustered into four categories. Our EEG microstate analysis revealed that VS patients with tinnitus exhibited an increased frequency of microstate C compared to those without tinnitus. Furthermore, correlation analysis demonstrated that the Tinnitus Handicap Inventory (THI) score was negatively associated with the duration of microstate A and positively associated with the frequency of microstate C. These findings suggest that the time series and syntax characteristics of EEG microstates differ significantly between VS patients with and without tinnitus, potentially reflecting abnormal allocation of neural resources and transition of functional brain activity. Our results provide a foundation for developing diverse treatments for tinnitus in VS patients.